?POSSIBLE MECHANISM OF ANTIHYPERGLYCEMIC EFFECT OF AZADIRACHTA INDICA LEAF EXTRACT: PART V (Biological Sciences - PJSIR, 2000)
Effect of Aradirachta indica leaf extract on adrenoreceptor blocking agents (propranolol and phentolamine) on serotonin inhibition in glucose mediated insulin release in rat pancreas was studied in vitro to elucidatethe possible mechanism of antihyperglycemic effect ofA. indica leaf extract. A indica leaf extract and phentolamine block significantly (P